2010
DOI: 10.1002/chem.200902924
|View full text |Cite
|
Sign up to set email alerts
|

Positive Homotropic Allosteric Receptors for Neutral Guests: Annulated Tetrathiafulvalene–Calix[4]pyrroles as Colorimetric Chemosensors for Nitroaromatic Explosives

Abstract: The study of positive homotropic allosterism in supramolecular receptors is important for elucidating design strategies that can lead to increased sensitivity in various molecular recognition applications. In this work, the cooperative relationship between tetrathiafulvalene (TTF)-calix[4]pyrroles and several nitroaromatic guests is examined. The design and synthesis of new annulated TTF-calix[4]pyrrole receptors with the goal of rigidifying the system to accommodate better nitroaromatic guests is outlined. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
60
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(64 citation statements)
references
References 59 publications
4
60
0
Order By: Relevance
“…This receptor has previously been demonstrated to bind TNB in organic solution. 5 However, although superior to earlier TTF-functionalized calixpyrrole receptors, is capable of detecting TNB in solution with a limit of detection of approximately 0.3 ppm in halogenated solvents. We have now incorporated this receptor on a cantilever sensor in the hopes of improving the sensitivity and creating a device capable detecting TNB vapors.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…This receptor has previously been demonstrated to bind TNB in organic solution. 5 However, although superior to earlier TTF-functionalized calixpyrrole receptors, is capable of detecting TNB in solution with a limit of detection of approximately 0.3 ppm in halogenated solvents. We have now incorporated this receptor on a cantilever sensor in the hopes of improving the sensitivity and creating a device capable detecting TNB vapors.…”
mentioning
confidence: 98%
“…[2][3][4][5] Their ease of use and their ability to function in the absence of any supporting instrumentation could make them applicable in certain-situations, where a qualitative yes/no indication involving the presence or absence of a targeted explosive is required. However, in spite of their potential advantages, the colorimetric sensors for nitroaromatic explosives reported to date suffer from disadvantages.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The large number of publications dealing with calixarenes is a reflection of their various applications. Calixarenes are receptors for neutral and charged species, [18][19][20] they form complexes with metal ions, [21][22][23] and are promising for environment protection due to their ability to extract Related to calixarenes also are the calixcrowns, 53,54 which are calixarenes bearing crown ether units; calixquinones, 55,56 containing one or two quinone units instead of phenol moieties of calixarenes; calixpyrroles, [57][58][59] built from pyrrole units, and calixphyrins, 60,61 formed by the reduction of porphyrins. Pillarenes, [62][63][64] in which benzene rings are linked by para, and not by meta positions as in calixarenes should also be included.…”
Section: Introductionmentioning
confidence: 99%
“…9 In this prior work (wherein anion affinities were not considered per se), it was concluded that 1 : 2 complexes, such as 2$(TNP) 2 and 2$(TNB) 2 , are formed, both in solution and in the solid state. This conclusion was reached on the basis of both continuous variation plots showing a maximum at 0.33 and X-ray crystallographic analyses.…”
mentioning
confidence: 99%